-2x+8+6x=-x-1

Simple and best practice solution for -2x+8+6x=-x-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+8+6x=-x-1 equation:


Simplifying
-2x + 8 + 6x = -1x + -1

Reorder the terms:
8 + -2x + 6x = -1x + -1

Combine like terms: -2x + 6x = 4x
8 + 4x = -1x + -1

Reorder the terms:
8 + 4x = -1 + -1x

Solving
8 + 4x = -1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
8 + 4x + x = -1 + -1x + x

Combine like terms: 4x + x = 5x
8 + 5x = -1 + -1x + x

Combine like terms: -1x + x = 0
8 + 5x = -1 + 0
8 + 5x = -1

Add '-8' to each side of the equation.
8 + -8 + 5x = -1 + -8

Combine like terms: 8 + -8 = 0
0 + 5x = -1 + -8
5x = -1 + -8

Combine like terms: -1 + -8 = -9
5x = -9

Divide each side by '5'.
x = -1.8

Simplifying
x = -1.8

See similar equations:

| 28t=560 | | 28t=260 | | 5a+14a+8= | | 4(2x-5)=-3(x-5) | | j/25=25 | | -5+2(x-5)=x+1 | | 15*x^4+3*x^3-76*x=0-76 | | logK=5 | | 870=g+3 | | 3(2x-1)=10 | | -15*x^4+3*x^3-76*x=0 | | 392=28f | | 15*x^4+3*x^3-76*x-70=0 | | 658=u+111 | | 15*x^4+3*x^3-76*x=0 | | 15w=420 | | n+69=973 | | 23c=851 | | 20LogK=-28 | | 12y=372 | | y+3xy+x=10x-10x | | 14j=406 | | k+217=855 | | x^2-4x+108=0 | | 8(3x^2+9x-4)= | | 77=y+10 | | sin^2(5x)=(1/3)cos^2(5x) | | s=27+50 | | h=30+55 | | 3x+2=2x+5+x | | 5x^2+4x+24=0 | | 2.4x^2-4x+24=0 |

Equations solver categories